Subject Matters of Nutrition Consultation and Claim of Food Advertisements in National Magazines and Tabloids - . Nurrohmah; . Hardinsyah; Sri Rihati Kusno (Media Gizi dan Keluarga, 2000)
The objectives of this study were to identity 1) nutrition complaints of youths and adults through Indonesian magazines and tabloids, and 2) the claims of advertisements of foods and food supplements in magazines and tabloids. Prior to 1997 there were only 4 national magazines and 3 national tabloids offered nutrition consultation column, and they were used as samples in this study. The results showed that readers profile of selected magazines and tabloids are mostly adult women, living in urban communities, blue and white collars, and housewives hold senior high school background. Most of the nutrition consultation clients were women (20-40 years old). There was no difference in nutrition status between men and women. Some questions (13,2%) considered they were overweight. The questions given were about food substitutes, ways to get healthy food, nutrient source foods and nutritional status. Most of the questions asked by the younger client were related to kinds and the way to get good food. The most frequently answers for the questions were given by explanation with suggestion (57,4%). The complete answer, which contains explanation, suggestion and menu instances, was only 24,4% from the whole answers. Food product advertisements consisted of 27,6% foods, 47,7% drinks, 13,8 % supplements and 10,8% foodstuffs. Generally, the advertisement¡¦s target were women. The most frequently claim is about ¡¥delicacy¡¦ and ¡¥the right nutrition¡¦. ¡¥The delicacy¡¦ and ¡¥the right nutrition¡¦ was claimed by 40,8%; ¡¥substance with specific function¡¦ is claimed by 28,7%, and ¡¥safety¡¦ was claimed by 6,3% of advertisements.